Emerging prediction methods for early diagnosis of necrotizing enterocolitis - Wu, Siyuan; Di, Sijia; Liu, Tianjing; Shi, Yongyan (Frontiers in Medicine, 2022)
Necrotizing enterocolitis (NEC) is a life-threatening disease of the digestive system that occurs in the neonatal period. NEC is difficult to diagnose early and the prognosis is poor. Previous studies have reported that abnormalities can be detected before the presentation of clinical symptoms. Based on an analysis of literature related to the early prediction of NEC, we provide a detailed review on the early prediction and diagnosis methods of NEC, including ultrasound, near-infrared spectroscopy, biomarkers, and intestinal microbiota. The aim of this review was to provide a reference for further research direction and clinical practice.